2013
DOI: 10.1128/jb.00993-13
|View full text |Cite
|
Sign up to set email alerts
|

The LuxR-Type Regulator VpsT Negatively Controls the Transcription of rpoS, Encoding the General Stress Response Regulator, in Vibrio cholerae Biofilms

Abstract: Cholera is a waterborne diarrheal disease caused by Vibrio cholerae strains of serogroups O1 and O139. Expression of the general stress response regulator RpoS and formation of biofilm communities enhance the capacity of V. cholerae to persist in aquatic environments. The transition of V. cholerae between free-swimming (planktonic) and biofilm life-styles is regulated by the second messenger cyclic di-GMP (c-di-GMP). We previously reported that increasing the c-di-GMP pool by overexpression of a diguanylate cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 52 publications
1
52
2
Order By: Relevance
“…The VpsT recognition sequence identified in this study is different from the one identified in the regulatory region of rpoS (AAAGGTTGTAAATC) (30). Thus, it appears that the VpsT recognition sequence can vary substantially.…”
Section: Determination Of Tss Of Vpslmentioning
confidence: 45%
See 2 more Smart Citations
“…The VpsT recognition sequence identified in this study is different from the one identified in the regulatory region of rpoS (AAAGGTTGTAAATC) (30). Thus, it appears that the VpsT recognition sequence can vary substantially.…”
Section: Determination Of Tss Of Vpslmentioning
confidence: 45%
“…Recent studies showed that VpsT can bind to the regulatory region of vpsL and rpoS in a c-di-GMP-dependent manner (25,30). Two inverted repeats were found in the VpsT recognition site at the rpoS promoter, yet this motif was not found in the regulatory region of vps genes (30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It also suppresses luxM by coupled degradation and activates aphA by revealing the ribosome binding site, while at the same time the sRNA is degraded (Feng et al, 2015). The activation of the translation of AphA (Rutherford et al, 2011; Van Kessel et al, 2013a) indirectly activates the transcription of virulence and biofilm genes, which promotes bacterial colonization and infection (Wang et al, 2014), so an important function of sRNAs in Vibrios is the link between QS and virulence (Carignan et al, 2016). Also, HapR/LuxR/SmcR/OpaR regulates the expression of genes involved in the synthesis and degradation of c-di-GMP reducing the levels of this second messenger that controls the switch between biofilm formation and motility and other fundamental bacterial behavior including fimbrial synthesis, T3SS and RNA modulation (Srivastava and Waters, 2012; Wang et al, 2014; Sengupta et al, 2016).…”
Section: Srnas Implicated In Processes Related To Virulence In Human mentioning
confidence: 99%
“…HapR negatively regulates the expression of aphA and directly suppresses biofilm formation by binding to the promoter of the gene vpsT , which codes a regulator of the exopolysaccharide production cluster vps , and indirectly through aphA , since AphA is a positive regulator of VpsT (Teschler et al, 2015; Carignan et al, 2016) ( Figure 1 ). HapR also suppresses the transcription of vpsR , which codes another transcription factor that also activates genes involved in biofilm formation and integrates signals from at least three different QS systems, which converge to the regulators of the LuxO response (Wang et al, 2014; Vakulskas et al, 2015) ( Figure 1 ).…”
Section: Srnas Implicated In Processes Related To Virulence In Human mentioning
confidence: 99%